Images every American should know: developing the Cultural Image Literacy Assessment-USA. Issue 4 (1st October 2016) - Emanuel, Richard; Baker, Kim; Challons-Lipton, Siu
Abstract: This paper describes the evolution of the Cultural Image Literacy Assessment-USA ©. This assessment represents an important first step in measuring image literacy within a culture. Visual literacy is an integral part of all cultures. The framework used in creating an assessment of cultural image literacy in the United States could be employed in developing measures of visual literacy for other cultures. In so doing, image literacy can be compared within and across cultures. This survey study explores the effects today's visual environments have on knowledge levels, and more importantly, knowledge gaps. The study builds on research relating to knowledge gap theory by describing the evolution of cultural image literacy assessment and providing current levels of image literacy within the United States. The final version of the assessment was distributed to undergraduate students ( N = 309) at a public university in the Southeast. Overall, respondents correctly identified an average of 68% of the images – a visual literacy grade of D. Respondents did better identifying general images followed by personalities, events and landmarks, and art and social movements. Implications for educators and education are discussed and future directions for this research are described.